Exploration of Sanmenxia Tourism from the Perspective of Cultural and Tourism Integration - Yu, Jieli (Journal of Theory and Practice of Engineering Science, 2023)
The proposal of the integration of culture and tourism has brought tremendous promotion to cultural inheritance and the development of the tourism industry. Different tourism regions have conducted in-depth research on the development of local tourism industry, taking into account the local tourism characteristics and cultural connotations. The tourism industry in Sanmenxia has an important impact on regional economic development and is an indispensable part of its national economic system. The development process of Sanmenxia tourism industry has significant problems that cannot be ignored, seriously reducing the realization of its tourism value. Therefore, in the context of cultural and tourism integration, it is necessary to actively explore new tourism models in Sanmenxia. This article takes Sanmenxia tourism as the research object, starting from the perspective of cultural tourism integration, briefly introduces cultural tourism integration and the overview of Sanmenxia tourism industry. Then, it analyzes the charm of Sanmenxia cultural tourism and the main problems in the development of Sanmenxia cultural tourism integration. Finally, it proposes a path for the integration of Sanmenxia culture and tourism industry, hoping to provide theoretical reference and more ideas for the sustainable development of Sanmenxia tourism industry.